Implications of artificial intelligence in healthcare delivery in the hospital settings: a literature review - Khaled, Nada; Alsabhan, Turki; Mahmud, Adalina (International Journal of Public Health and Clinical Sciences (IJPHCS), 2019)
Background: With massive development of artificial intelligence in all industries, the development of artificial intelligence technology in healthcare considered delayed compared with other field. The slow development of healthcare related to many factors including financial, ethical and social among other contributors. The aim of this literature is to review the positive and negative implications of artificial intelligence in healthcare delivery in hospital setting. Literature review aims to review the positive and negative implications of artificial intelligence in healthcare delivery in hospital settings, and reviews the various aspects of uses and applications of artificial intelligence in healthcare delivery in hospital setting in implications of artificial intelligence in healthcare delivery in hospital settings. Result: Most available studies showed that artificial intelligence has positively influence the heath care delivery in terms of quality of care, efficiency and accuracy. On the other hand, several studies showed that AI can also have negative implications in terms of ethical, privacy and de-humanization of care. Conclusion: In conclusion, the positive implication of artificial intelligence and the wide range opportunity of technological development exceed the negative aspect, especially when the negative aspects are addressed appropriately or avoided.